2012
DOI: 10.1155/2012/807294
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impacts of Whale-Watching

Abstract: Whale watching is an international industry worth more than US$2 billion globally and is currently the greatest economic activity reliant upon cetaceans. However, there is concern that whale watching is detrimental to the target species. Numerous studies have shown that cetaceans exhibit behavioral changes in response to whale-watching boat traffic. Some of these behavioral changes involve inhibiting biologically important behaviors such as feeding and resting. There is convincing evidence for some species tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
118
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 73 publications
1
118
0
6
Order By: Relevance
“…Compared with captive facilities, responsible boatbased cetacean watching has been promoted as an ethically acceptable option for observing dolphins, providing a valuable forum for environmental education and promotion of conservation efforts (IFAW, 1997). However, a considerable body of work has shown that boats and boat-based cetacean watching can have multiple negative impacts on the behaviour of the focal individual, population or species (Parsons, 2012). Short-term impacts associated with boat interactions include group directional changes (Steckenreuter, Möller, & Harcourt, 2012;, changes in group dispersion (Arcangeli & Crosti, 2009;Steckenreuter et al, 2012), heightened breathing synchrony (Hastie, Wilson, Tufft, & Thompson, 2003), increased dive times (Lusseau, 2003b) and changes in vocalizations (Buckstaff, 2004;Scarpaci, Bigger, Corkeron, & Nugegoda, 2000).…”
mentioning
confidence: 99%
“…Compared with captive facilities, responsible boatbased cetacean watching has been promoted as an ethically acceptable option for observing dolphins, providing a valuable forum for environmental education and promotion of conservation efforts (IFAW, 1997). However, a considerable body of work has shown that boats and boat-based cetacean watching can have multiple negative impacts on the behaviour of the focal individual, population or species (Parsons, 2012). Short-term impacts associated with boat interactions include group directional changes (Steckenreuter, Möller, & Harcourt, 2012;, changes in group dispersion (Arcangeli & Crosti, 2009;Steckenreuter et al, 2012), heightened breathing synchrony (Hastie, Wilson, Tufft, & Thompson, 2003), increased dive times (Lusseau, 2003b) and changes in vocalizations (Buckstaff, 2004;Scarpaci, Bigger, Corkeron, & Nugegoda, 2000).…”
mentioning
confidence: 99%
“…The question scientists, policy-makers and tourism industry leaders are facing is how to determine the conditions under which whale-watching becomes harmful to the animals at stake, and how to best protect them (e.g. Catlin, Jones and Jones, 2012;Carlson, 2012;Higham and Lusseau, 2004;Parsons, 2012;Simmonds and Isaac, 2007;Steckenreuter, Harcourt and Mӧller, 2012;Visser et al, 2010). Here is evidence that the regulations which many are currently seeking to introduce may not work in communities like this, given its internal tensions.…”
Section: Discussionmentioning
confidence: 99%
“…Carlson, 2012;Garrod and Fennel, 2004), but of course compliance with them is not guaranteed (e.g. Parsons, 2012;Quiros, 2007).…”
mentioning
confidence: 99%
“…Vessel traffic may alter marine mammal behaviour through their physical presence, elevated underwater noise levels and exposure to collision risks (Richardson et al 1995, Laist et al 2001, Nowacek et al 2007, Clark et al 2009, Parsons 2012, Pirotta et al 2015. Whale-watching, a form of vessel traffic in which boat operators and tourists specifically seek to interact with marine mammals, is a lucrative business that has developed rapidly and widely over the past decades (O'Connor et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This type of activity has been repeatedly shown to elicit short-term behavioural responses from a variety of marine mammal species (e.g. Richardson et al 1995, Parsons 2012, Senigaglia et al 2016 for reviews). Such changes in behaviour can result in increased energetic expenditures or decreased energetic gains (e.g.…”
Section: Introductionmentioning
confidence: 99%